PREDIKSI MINAT DAN PEMBELIAN ASURANSI SYARIAH DI KALANGAN APARATUR SIPIL NEGARA (ASN) DI PROVINSI ACEH - Odos, Fransiska Andriyani; Wijaya, Chandra Setya; Khalid, Miqsyal; Tamara, Dewi (JURNAL ILMIAH EDUNOMIKA, 2024)
The implementation of the Qanun on Sharia Financial Institutions in Aceh Province has resulted in the exit of conventional financial institutions which is expected to be a big opportunity for the sharia insurance industry in Aceh province. This research uses quantitative analysis and data collection methods using questionnaires on ASN in Aceh Province and the data is analyzed using Smart PLS. The research results show that Islamic Financial Literacy has a positive effect on Attitudes towards Sharia Insurance, Perceived Benefits has a positive effect on Attitudes towards Sharia Insurance, Perceived Behavioral Control has a positive effect on Attitudes towards Sharia Insurance, Attitudes towards Sharia Insurance have a positive effect on Intention to Purchase Sharia Insurance, and Islamic Financial Literacy, perceived benefits, subjective norms and perceived behavioral control have a significant positive relationship with Intention to Purchase Sharia Insurance, mediated by attitudes towards sharia insurance.